2022
DOI: 10.1002/ptr.7600
|View full text |Cite
|
Sign up to set email alerts
|

The effect of saffron (Crocus sativus L.) on glycemia, lipid profile, and antioxidant status in patients with type‐2 diabetes mellitus: A randomized placebo‐controlled trial

Abstract: In the current study, we aimed to investigate the effect of saffron supplementation on glycemic status, lipid profile, atherogenic indices, and oxidative status in patients with type‐2 diabetes (T2DM). In a randomized, double‐blind controlled trial, 70 patients were randomly allocated into two groups (n = 35, each) and received 100 mg/day of saffron or placebo for eight weeks. Dietary intake, weight, body mass index (BMI), waist and hip circumferences (WC and HC), waist to hip ratio (WHR), fasting blood sugar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 42 publications
0
7
0
1
Order By: Relevance
“…Moreover, it was also noted that saffron plus damask rose petals reduced weight gain, TG, and CRP (all p < 0.05) compared to the control group in a study using diabetic male Sprague Dawley rats [64]. It is also known that saffron supplementation can alleviate DM2 by improving the glycaemic status, lipid profile, liver enzymes, and oxidative status [65]; however, the mechanism of the effect of saffron on the modification of the weight in AA and/or RA remains unclear.…”
Section: Discussionmentioning
confidence: 90%
“…Moreover, it was also noted that saffron plus damask rose petals reduced weight gain, TG, and CRP (all p < 0.05) compared to the control group in a study using diabetic male Sprague Dawley rats [64]. It is also known that saffron supplementation can alleviate DM2 by improving the glycaemic status, lipid profile, liver enzymes, and oxidative status [65]; however, the mechanism of the effect of saffron on the modification of the weight in AA and/or RA remains unclear.…”
Section: Discussionmentioning
confidence: 90%
“…In einem Umbrella-Review wurden 23 systematische Reviews (SR) zu Safran zusammengefasst: 13 SRs bei Depressionen, 6 SRs bei sexueller Dysfunktion und je 3 SRs bei Ängsten und Hirnleistungsstörungen [36]. Darüber hinaus geben Metaanalysen Hinweise, dass Safran auch bei Diabetes Typ 2 [11,26,32] mit oder ohne metabolischem Syndrom [13,37] wirksam ist, beim prämenstruellen Syndrom (PMS), bei Postpartum-Depressionen, Schlafstörungen und Essstörungen [22,27,36] sowie bei Stoffwechselstörungen wie Arteriosklerose, Fettstoffwechselstörung, bei Augenkrankheiten (Makuladegeneration, diabetischer Retinopathie, Glaukom, Retinitis pigmentosa) [12,23,34,38] und bei Infektionen mit SARS-CoV-2 [41]. Die blutdrucksenkende Wirkung ist vermutlich klinisch nicht relevant [35].…”
Section: Indikationenunclassified
“…Published research results have repeatedly confirmed that saffron can improve the increase of blood glucose and blood pressure caused by MetS and related diseases [4][5][6], protect vascular endothelial function, and even delay the process of diabetic nephropathy [7]. However, the effects of crocin on metabolic diseases vary in different clinical studies.…”
Section: Introductionmentioning
confidence: 99%
“…Aynaz Tajaddini et al revealed through clinical studies that safflower intervention can effectively reduce FBG, blood lipids, and liver enzymes, and improve oxidative status in type 2 diabetes mellitus (T2DM) [6]. However, Samaneh Sepahi et al considered that there was no significant change in blood lipids and liver enzymes after crocin intervention in T2DM [10].…”
Section: Introductionmentioning
confidence: 99%